If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 3(v + -2) Reorder the terms: 12 = 3(-2 + v) 12 = (-2 * 3 + v * 3) 12 = (-6 + 3v) Solving 12 = -6 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. 12 + -3v = -6 + 3v + -3v Combine like terms: 3v + -3v = 0 12 + -3v = -6 + 0 12 + -3v = -6 Add '-12' to each side of the equation. 12 + -12 + -3v = -6 + -12 Combine like terms: 12 + -12 = 0 0 + -3v = -6 + -12 -3v = -6 + -12 Combine like terms: -6 + -12 = -18 -3v = -18 Divide each side by '-3'. v = 6 Simplifying v = 6
| X=1.45 | | F(3)=4x-9 | | 1/3(2x-5)=6 | | 3g-2h=5 | | n-1+7n=7 | | 15=-15/8v | | X+47=-29 | | W+3=24 | | -20=3a+7a | | 15+3B=-3(1-3B) | | (2x-2)+2(3x+7)=5x-3 | | 8+4a=5a+6 | | 2x-.05=x | | -3.75t+32=-8.5 | | 3x-2(x-1)=-4+3x+8 | | G(-3)=-3*3-(-3) | | 30(3+7)+40x=30+600 | | 8b+6-3=-5 | | 14=-8x+x | | 7x^2+68x+25=0 | | 3c+-2=-2-9c | | r/-3=2 | | -7k+21= | | x+28=3x+45 | | 4x+.33=.5x+5.5 | | 45=4x+7 | | 3(x-5)+18=2(2+4) | | 8x^3+50x=0 | | 3a^2-10a-125=0 | | 3+9n-2=2n+4-3n | | (125x-108)/(14x-15)=8 | | K=2/3tc |